1997
DOI: 10.1136/jech.51.6.711
|View full text |Cite
|
Sign up to set email alerts
|

Pure tone audiometry and impedance screening of school entrant children by nurses: evaluation in a practical setting.

Abstract: Background-Screening for hearing loss in English children at entry to school (age 5-6 years) is usually by pure tone audiometry sweep undertaken by school nurses. This study aimed to compare the validity and screening rates of pure tone audiometry with impedance screening in these children. Methods-Two stage pure tone audiometry and impedance methods of screening were compared in 610 school entry children from 19 infant schools in north east England. Both procedures were completed by school nurses. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
6

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 5 publications
1
11
1
6
Order By: Relevance
“…The correlation coefficient was found with a value of r = 0.23, which suggested that the two data-sets are not well related. In a previous study by Holtby et al on hearing screening [17], the tympanometric data from 610 English school children showed a sensitivity of 74.4%, but a PPV of 37.6%. The discrepancy between the data from the present and the Holtby study is probably procedural, since in the latter the tympanometric measurements were taken twice, following the typical 3-stage neonatal screening paradigm [1].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The correlation coefficient was found with a value of r = 0.23, which suggested that the two data-sets are not well related. In a previous study by Holtby et al on hearing screening [17], the tympanometric data from 610 English school children showed a sensitivity of 74.4%, but a PPV of 37.6%. The discrepancy between the data from the present and the Holtby study is probably procedural, since in the latter the tympanometric measurements were taken twice, following the typical 3-stage neonatal screening paradigm [1].…”
Section: Discussionmentioning
confidence: 95%
“…Each procedure was compared to an in situ conventional pure-tone audiometry. While screening procedures based on tympanometry and otoacoustic emissions have been previously field-tested in various school environments [6,7,[16][17][18], the automated screening audiometry is relatively new. Positive feedback on the use of automated audiometry in screening has been recently reported by McPherson et al [19], in a study on 80 school children tested with automated and conventional audiometry.…”
Section: Discussionmentioning
confidence: 99%
“…Five evaluations reported in four studies [36][37][38][39] included in the original 2007 HTA report and three 17,27,30 in the current update evaluated the accuracy of audiometry-based tests. The original five studies, all assessing pure-tone sweep devices, reported sensitivities ranging from 86% to 100% and specificities from 65% to 99%.…”
Section: Audiometry-based Testsmentioning
confidence: 99%
“…Os testes audiométricos, realizados por meio de aparelhos eletrônicos são os seguintes: audiometria de tons puros, logoaudiometria, audiometria de potenciais evocados auditivos, audiometria de reforço visual e audiometria de jogo, audiometria de campo livre e otoemissões acústicas. O tipo de teste e o aparelho utilizados deverão ser de acordo com a faixa etária, a atitude, a cooperação da criança e a suspeita diagnósti-ca [9][10][11] .…”
Section: Introductionunclassified